Contribution of gradient-echo MRI in the study of subacromial pathology: correlation between surgery and arthrography - Pigeau, I; Doursounian, L; Sokolow, C; Valenti, P; Djermag, Y; Maigne, J Y; Gaudillat, C; Frija, G (Annales de radiologie, 1992)
30 asymptomatic volunteer subjects and more than 400 patients with suspected rotator cuff lesions were examined by MRI at 0.5 T using T2*-PD weighted gradient echo (T2-GEI) sequences. Its superiority over T2 spin echo imaging was established in previous studies. The results were compared to those of surgery in 87 cases and arthrography in 233 cases (associated with CT arthrography in 70 cases). In the operated patients, T2-GEI and arthrography correctly diagnosed 49 complete ruptures (CR). T2-GEI was found to be superior to arthrography for defining the real extent of the rupture, the degree of tendon retraction and the local muscular trophicity, essential information to define the therapeutic indications. In contrast, among 22 lesions of the long biceps tendon, correctly demonstrated by arthrography or CT arthrography, 5 intracapsular lesions were not detected by MRI. MRI was able to detect 8 lesions of the anterior labrum associated with a CR not demonstrated by arthrography. Lastly, among the 18 cases of partial inferior rupture (PIR), 6 partial superficial ruptures and 14 cases of inflammatory changes, correctly diagnosed by MRI, only 8 PIR were also demonstrated by arthrography. For the non-operated patients investigated by the two modalities (146 cases), T2-GEI and arthrography were concordant in 43 cases. In contrast, 103 intact cuffs on arthrography showed features on T2-GEI compatible with tendinopathy without rupture, bursitis and degenerative changes. In the absence of very fine surgical or histological correlations for these small lesions, it is impossible, at the present time, to determine the real sensitivity and specificity of MRI.